2016
DOI: 10.1111/ap.12172
|View full text |Cite
|
Sign up to set email alerts
|

Family Interventions in Psychosis: A Review of the Evidence and Barriers to Implementation

Abstract: Objective: Family interventions for schizophrenia are recommended psychological interventions worldwide. The National Institute for Care and Clinical Excellence (UK) and the Royal Australian and New Zealand College of Psychiatrists recommend family interventions as a first-line treatment and "treatment essential," respectively, at all stages of psychosis and with all aspects of care. However, the success of the integration of these interventions into routine clinical services has been problematic and remains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 39 publications
5
85
0
3
Order By: Relevance
“…Despite an emerging evidence base for family interventions in early psychosis, and indeed a well-established evidence base for family interventions in chronic psychosis, the availability of these interventions in routine care is poor because of barriers at the level of services, clinician expertise, and the service user [71]. In addition, on entry into specialist first-episode services, carers often face an uncertain long-term prognosis for their relative and a process of recovery that extends well beyond the available 2-year period of care provided by state-supported specialist FEP care.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an emerging evidence base for family interventions in early psychosis, and indeed a well-established evidence base for family interventions in chronic psychosis, the availability of these interventions in routine care is poor because of barriers at the level of services, clinician expertise, and the service user [71]. In addition, on entry into specialist first-episode services, carers often face an uncertain long-term prognosis for their relative and a process of recovery that extends well beyond the available 2-year period of care provided by state-supported specialist FEP care.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of evidence‐based practices in tertiary mental health settings has been associated with challenges such as engagement of staff and families, concerns regarding manualised approaches, and fidelity (Addis, Wade, & Hatgis, ; Albers, Mildon, Lyon, & Shlonsky, ; Berry & Haddock, ; Bucci, Berry, Barrowclough, & Haddock, ). These concerns have led to suggestions that scientific evidence for emerging innovation may not be enough to produce practice change (Urquhart et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of implementation of family therapies for schizophrenia reported implementation rates of between 0% and 50% (Bucci et al., ). Kavanagh et al.…”
Section: Introductionmentioning
confidence: 99%
“…Bucci et al, 2016) may offer a partial answer if it is adequately resourced, and dedicated staffing would address the competing role demands experienced by case managers (Onwemere et al, 2016). Bucci et al, 2016) may offer a partial answer if it is adequately resourced, and dedicated staffing would address the competing role demands experienced by case managers (Onwemere et al, 2016).…”
Section: Contextual Fit Of the Interventionmentioning
confidence: 99%
“…A stepped-care approach is probably essential (Bucci et al, 2016): as Onwemere et al (2016) argue, many families may only be seeking information, or a brief, targeted intervention for a specific problem. A stepped-care approach is probably essential (Bucci et al, 2016): as Onwemere et al (2016) argue, many families may only be seeking information, or a brief, targeted intervention for a specific problem.…”
Section: Contextual Fit Of the Interventionmentioning
confidence: 99%